Evaluation of Revenue Collection Fees for Acquisition Duty of Right on Land and Building at the Bandung City Revenue Management Agency in 2020-2023 - Danie, Danie Saputra Priyatna (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Regional taxes are mandatory contributions imposed on individuals or entities to their regions. Regional taxes will later be used by the regional government to finance its own region, so the role of regional taxes is very much needed by the regional government in running the wheels of government. Since the implementation of regional autonomy, each region has been required to compete in developing their respective regions. One of the benefits of regional taxes is the existence of development in the region, such as road repairs, bridge repairs, development of infrastructure and facilities in the region. This study focuses on the realization of BPHTB tax in Bandung City. The realization figure for BPHTB tax in Bandung City in 2020-2023 was always below target, and the realization figure for BPHTB tax in Bandung City was the lowest of the nine other regional taxes, therefore the author wanted to know what kind of evaluation was carried out by the Bandung City Government in handling this. This study uses a qualitative descriptive method. Data collection comes from primary data and secondary data. The data collection techniques used are in-depth interviews, observations, and literature studies. With this research, it is hoped that in the future the realization of BPHTB tax revenue in Bandung City will increase in accordance with the targets set by the Bandung City Government.